Supra-subduction zone magmatism of the Koçali ophiolite, SE Turkey. (May 2017) - Beyarslan, Melahat
Abstract: The Late Cretaceous Koçali ophiolite is an important element within the southeastern Anatolian ophiolite belt and contains all components of a complete ophiolite, including mantle peridotites (harzburgites, and subordinate dunite) gabbros, sheeted dyke complexes, lower volcanic unit (pillowed basalts), and upper volcanic unit (andesite and andesitic pyroclastics) plagiogranite and ultramafic rocks intruded into the gabbros. All components of the Koçali ophiolites show strong suprasubduction-zone affinities, from harzburgitic mantle to basaltic lavas. The radiolarian faunas and geochronological data indicate that there are two different volcanic units: Tarasa volcanics and volcanics of the Koçali ophiolite. While the Tarasa volcanics are of Carnian to Rhaetian age, the Koçali ophiolite is of the Late Cretaceous age. The geochemical features indicate an E-MORB source for the Tarasa volcanics, and a forearc source for the Koçali ophiolite. Highlights: Koçali Complex consists of the Carnian to Rhaetian Tarasa volcanics and the Cretaceous Koçali ophiolite. Koçali ophiolite is remnant of the south branch of Neotethys. Koçali ophiolite developed in fore-arc setting in a supra-subduction zone (SSZ) environment.